If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(x + -1) + 1 = -19 Reorder the terms: 4(-1 + x) + 1 = -19 (-1 * 4 + x * 4) + 1 = -19 (-4 + 4x) + 1 = -19 Reorder the terms: -4 + 1 + 4x = -19 Combine like terms: -4 + 1 = -3 -3 + 4x = -19 Solving -3 + 4x = -19 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + 4x = -19 + 3 Combine like terms: -3 + 3 = 0 0 + 4x = -19 + 3 4x = -19 + 3 Combine like terms: -19 + 3 = -16 4x = -16 Divide each side by '4'. x = -4 Simplifying x = -4
| 3x-40=3(3x+4)+8 | | 4x-6=5(x-4)+8 | | -x-14=4(3x+3) | | -8=2(2x+2) | | 4(3x-2)-8=3x+29 | | -15=5(x-2) | | -3x-26=2(2x-4)+3 | | (64x^3+125)+(-8x^2-100x)=0 | | 10x-23=27 | | -33=3(x-2) | | -7x-5=-6x+2 | | 2x-26=-40 | | 2x-45=3(5x-2) | | 4x-48=3(5x-1)-1 | | 3(5x-5)-8=-8 | | -13+3r=-39+25r | | 2m+4m=10 | | 49=3(2x-1)+4 | | -7x+28=-70 | | 4(x-2)-6=5x-8 | | 3=3(3x+4) | | 5(4x+3)=x-4 | | 24=2(2x-4) | | -5x-41=4(5x-4) | | 5r+10=-120-8r | | 64x^3+125-8x^2-100x=0 | | 4(4x-2)=4x-20 | | 5x+25=5(2x-4) | | x-18=-7 | | 31-2r=10-9r | | 5(x+5)+1=-19 | | -16=4(x-5) |